Role of plasminogen activator inhibitor and free fatty acids in diagnosis of insulin resistance in patients with myocardial infarction - Olga Viktorovna Gruzdeva; Olga Leonidovna Barbarash; Olga Evgen'evna Akbasheva; Tatiana Sergeevna Fedorova; Elena Ivanovna Palicheva; Vasil'evich Kashtalap; Yulia Alexandrovna Dyleva; Anna Alexandrovna Silonova; Ekaterina Vladimirovna Sionina; Evgenia Gennad'evna Uchasova (Сахарный диабет)
Aim. Evaluation of the dynamics of the markers of insulin resistance in patients with myocardial infarction with ST-segment elevation with andwithout type 2 diabetes mellitus in the acute and early recovery period of the disease. Materials and methods. The study included 95 patients with myocardial infarction and 60 patients with myocardial infarction and type 2 diabetes.The control group consisted of 30 persons. We all studied at 1 st and 12 th day of myocardial infarction was determined by the content of free fattyacids, glucose, C-peptide, insulin in serum and plasminogen activator inhibitor in blood plasma. In addition, the 12 th day was determined postprandialglycemic, insulin and C-peptide 2h after a standard carbohydrate breakfast. Results. It is established that during myocardial infarction accompanied by the development of insulin resistance, characterized by postprandialglycemia and insulinemia, as well as the presence of elevated levels of free fatty acids, plasminogen activator inhibitor. Conclusion. The definition of metabolic markers of insulin resistance may be of great predictive capacity for assessing the risk of both acute coronaryevents and select tactics to further treatment